Analisis perbandingan sikap konsumen terhadap Toyota Avanza dan Daihatsu Xenia di Pekanbaru - Sri Ayu Wulandari; Lilis Sulistyowati; Aida Nursanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research aim to to analyse do there is difference of consumer attitude factor in buying brand car of Toyota AVANZA and of Daihatsu XENIA influenced by product, brand, promotion and price.Study sampling accidental the uses This of technique selected 100 samples. Methods data qualitative of method a is study this in used Analysis of analysis, data quantitative of analysis test different of analysis and.From result of examination which have been, There are difference which is consumer attitude signifikan to Toyota Avanza and of Daihatasu Xenia pursuant to product variable. And known that product of Toyota compared to nicer Avanza of Daihatsu Xenia. There are difference which is consumer attitude signifikan to Toyota Avanza and of Daihatasu Xenia pursuant to brand variable. From is the result known that Toyota Avanza more have brand to compared to Daihatsu Xenia. Do not there are difference which is consumer attitude signifikan to Toyota Avanza and of Daihatasu Xenia pursuant to price variable. From is the result known that price of Daihatsu Xenia more reached to be to be compared to Toyota Avanza. Do not there are difference which is consumer attitude signifikan to Toyota Avanza and of Daihatasu Xenia pursuant to promotion variable. From is the result known that promotion of Daihatsu Xenia more is effective compared to Toyota Avanza.Keywords: product, brand, price, attitudes consumer and promotion.